Evaluation of different ready-mixed insecticides against jassid in summer sesame: EVALUATION OF DIFFERENT READY-MIXED INSECTICIDES AGAINST JASSID IN SUMMER SESAME - V N TRIVEDI,; J B BHUT,; K N GAMI ,; A D MORDIYA, (Journal of Oilseeds Research, 2025)
A field experiment was conducted to evaluate the different ready mixed insecticides against jassid (Orosius albicinctus) in summer sesame. Among the different nine ready-mixed insecticides evaluated, the lowest (1.05 jassids/3 leaves/plant) population of jassid was recorded in treatment of pyriproxyfen 8% + dinotefuron 5% + diafenthiuron 18% SC 0.047 % which was statistically at par with diafenthiuron 25% + pyriproxyfen 5% SE 0.008% (1.16 jassids/3 leaves/plant) and acephate 50% + imidacloprid 1.8% SP 0.10% (1.22 jassids/3 leaves/plant) after 3 days of the first spray. A similar trend was seen after 7, 10 and 14 days after first spray as well as 3, 7, 10 and 14 days after second spray. The highest (1117 kg/ha) seed yield was recorded in the plot treated with pyriproxyfen 8% + dinotefuron 5% + diafenthiuron 18% SC 0.047 %. The highest ICBR (1:21.6) was found in diafenthiuron 25% + pyriproxyfen 5% SE 0.008%.